2021
DOI: 10.1177/0143831x21995259
|View full text |Cite
|
Sign up to set email alerts
|

Flexible working practices and job-related anxiety: Examining the roles of trust in management and job autonomy

Abstract: Although flexible working practices (FWPs) have been associated with positive individual outcomes, less is known about ‘how’ and ‘why’ such associations occur. Drawing on Conservation of Resources theory, this study examines the mediating and moderating processes which underpin the relationship between FWPs and job-related anxiety. The study’s hypotheses, proposing a moderated mediation model, are tested using data from Britain’s Workplace Employment Relations Survey (WERS) 2011. The results of generalised mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 128 publications
0
4
0
Order By: Relevance
“…The significant increase during the pandemic in the dimension Adequate Working Time and Workload may suggest that workers' flexibilisation of time management during this period was appropriate. A possible explanation is that workers' perception of their flexibility at work facilitates the work-life balance [33] and helps strengthen trust within the organisations [34]. Despite the restrictions of the coronavirus context, the social isolation in Portugal possibly helped workers rediscover family values and relationships by valuing more unity and time with family [35].…”
Section: Discussionmentioning
confidence: 99%
“…The significant increase during the pandemic in the dimension Adequate Working Time and Workload may suggest that workers' flexibilisation of time management during this period was appropriate. A possible explanation is that workers' perception of their flexibility at work facilitates the work-life balance [33] and helps strengthen trust within the organisations [34]. Despite the restrictions of the coronavirus context, the social isolation in Portugal possibly helped workers rediscover family values and relationships by valuing more unity and time with family [35].…”
Section: Discussionmentioning
confidence: 99%
“…Trust is the glue in responsible autonomy. More specifically, successful WFH is highly contingent upon reciprocal trust between employers and employees, best supported by institutionalised trust embedded in good employment relationships (Fox, 1974;Siebert et al, 2015;Yunus and Mostafa, 2022). Fox's (1974) analysis that high discretion/high trust (responsible autonomy) dynamics are most likely in occupations like professional work is relevant to our research.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult for individuals who are physically and mentally fatigued or in a bad frame of mind to take the initiative and become more innovative. In contrast, FWA creates a good working environment and reduces work conflict and stress ( Yunus and Mostafa, 2021 ), which encourages employees to proactively invest useful resources such as time, attention, and energy into their work. Grzywacz et al (2008) showed that FWA significantly improved employee wellness, which in turn helped improve their work engagement.…”
Section: Theory and Hypothesesmentioning
confidence: 99%